Nitric Oxide synthesis is depressed in Bos indicus cattle infected with Trypanosoma congolense and Trypanosoma vivax and does not mediate T-cell suppression - Taylor, K.; Lutje, V.; Mertens, B. (1996)
Infection with African trypanosomes causes the diseases sleeping sickness in humans and nagana in cattle in sub-Saharan Africa. Suppression of cellular immune responses is a feature of trypanosomiasis in bovine, human, and murine hosts. Some aspects of immunosuppression in the murine model are mediated by nitric oxide (NO) produced by gamma interferon (IFN-gamma)-activated macrophages. We have investigated whether a similar mechanism is responsibe for T-cell unresponsiveness in bovine trypanosomiasis. Bovine monocytes and macrophages from uninfected cattle and activated in vitro with IFN-gamma produced NO; however, this response was down-regulated in infected cattle. Similarly, the expression of inducible NO synthase messenger RNA was depressed in macrophages of infected cattle. Proliferation of mononuclear cells of trypanosome infected cattle cultured with mitogen or trypanosome antigens was unchanged by the addition of an NO synthase inhibitor. Lymphocytes of infected cattle secreted interleukins with T-cell growth factor activity after in vitro activation with mitogens but not after activation with trypanosome antigens. Although lymph node cells secreted IFN-gamma after in vitro activation, ex vivo expression of mRNA was depressed. In contrast, the level of expression of interleukin 10 mRNA was higher during infection. We conclude that NO is not involved in the loss of T-cell proliferative function associated with trypanosomiasis in cattle and that, in contrast to the mouse model, the capacity of monocytes and macrophages to produce NO is actually down-regulated in infected cattle.